BONE GROWING AND DEVELOPMENT ALTERATIONS IN ALBINO RATS WITH A FAULTY PROTEIN DIET ANO DIFFERENT !RON CONCENTRATIONS - Cáceres Gutiérrez, Lita Amanda (2004)
The main research objeetive was to determine the effect that proteins and iron have; when they are included in the diet, over bone growing and development in Holztman albino rats 21 days old. They were divided in 4 experimental group: Al ( protein lOg., iron 29mg.), A2 (protein lOg., iron 46mg.), Bl(protein 5g., iron 29mg.), B2 (protein 5g., iron 46mg.) and were sacrificed 46 days after research beginning. There were taken cranium facial Skeleton, mandible and femur measures and they were stained with hemotixilin- eosin, Schiff peryodic acid and Potassic ferrocianurun. Our resuIts show that growing and deve/omen! of rats is directly related with protein and concentration of consumed dieto Weight and length of Craniofacial skeleton,mandible femur as well as number of osteoblasts, osteocites,osteclasts and hemosiderin of A groups were significantly greater in the relation with B groups. Growing and development of Bl group was smaller in relation with Al group.